A survey of the global impact of COVID‐19 on the practice of pediatric anesthesia: A study from the pediatric anesthesia COVID‐19 Collaborative Group. Issue 6 (3rd May 2021) - Soneru, Codruta N.; Fernandez, Allison M.; Bradford, Victoria; Staffa, Steven J.; Raman, Vidya T.; Cravero, Joseph; Zurakowski, David; Meier, Petra M.; ,
Abstract: Background: Pediatric anesthesiology has been greatly impacted by COVID‐19 in the delivery of care to patients and to the individual providers. With this study, we sought to survey pediatric centers and highlight the variations in care related to perioperative medicine during the COVID‐19 pandemic, including the availability of protective equipment, the practice of pediatric anesthesia, and economic impact. Aim: The aim of the survey was to determine how COVID‐19 directly impacted pediatric anesthesia practices during the study period. Methods: A survey concerning four major domains (testing, safety, clinical management/policy, economics) was developed. It was pilot tested for clarity and content by members of the Pediatric Anesthesia COVID‐19 Collaborative. The survey was administered by email to all Pediatric Anesthesia COVID‐19 Collaborative members on September 1, 2020. Respondents had six weeks to complete the survey and were instructed to answer the questions based on their institution's practice during September 1 ‐ October 13, 2020. Results: Sixty‐three institutions (100% response rate) participated in the COVID‐19 Pediatric Anesthesia Survey. Forty‐one hospitals (65%) were from the United States, and 35% included other countries. N95 masks were available to anesthesia teams at 91% of institutions (n = 57) (95% CI: 80%–96%). COVID‐19 testing criteria of anesthesia staff and guidelines to return to work varied by institution. Structured simulation training aimed at improving COVID‐19 safety and patient care occurred at 62% of institutions (n = 39). Pediatric anesthesiologists were economically affected by a reduction in their employer benefits and restriction of travel due to employer imposed quarantine regulations. Conclusion: Our data indicate that the COVID‐19 pandemic has impacted the testing, safety, clinical management, and economics of pediatric anesthesia practice. Further investigation into the long‐term consequences for the specialty is indicated.